2014
DOI: 10.1590/0074-0276140273
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of influenza A related to climatic conditions during and after a pandemic period in the city of Salvador, northeastern Brazil

Abstract: During the influenza pandemic of 2009, the A(H1N1)pdm09, A/H3N2 seasonal and influenza B viruses were observed to be co-circulating with other respiratory viruses. To observe the epidemiological pattern of the influenza virus between May 2009-August 2011, 467 nasopharyngeal aspirates were collected from children less than five years of age in the city of Salvador. In addition, data on weather conditions were obtained. Indirect immunofluorescence, real-time transcription reverse polymerase chain reaction (RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…As a result of our study, among the total of reported cases, the highest frequency occurred in females, children and young adults who are white, with an educational level of completed high school and residents in urban areas were the most frequently notified, as well as confirmed cases of influenza A(H1N1)pdm09 were found. Such findings are supported by results of other authors 20,21,[23][24][25][26][27][28] .…”
Section: Description By Time Place and Individualsupporting
confidence: 91%
See 1 more Smart Citation
“…As a result of our study, among the total of reported cases, the highest frequency occurred in females, children and young adults who are white, with an educational level of completed high school and residents in urban areas were the most frequently notified, as well as confirmed cases of influenza A(H1N1)pdm09 were found. Such findings are supported by results of other authors 20,21,[23][24][25][26][27][28] .…”
Section: Description By Time Place and Individualsupporting
confidence: 91%
“…The national tendency is that the influenza virus spreads in the south and southeast regions during winter (June-August) and in the north and northeast regions, during rainy periods. However, in tropical and subtropical countries, there may be peaks during the year in the dynamics of the seasonal influenza A; some authors suggest that this behavior is associated with climate aspects (temperature, humidity), solar radiation, possibly with levels of vitamin D, the host immunity and the virulence of the viral strain 23 .…”
Section: Description By Time Place and Individualmentioning
confidence: 99%
“…16 This same group also reported their attempt to investigate parainfluenza infections among children from Fortaleza, 22 as well as adenovirus infections in Salvador. 23 Silva et al 24 assessed the prevalence of influenza viruses among children in Salvador. RSV infects virtually every child in the 1st few years of life and is the most important cause of hospitalization for respiratory infection in young children worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,20 Only a few studies were conducted to investigate the prevalence and seasonal patterns of different viral infections among children with an episode of LRTI seen at hospitals from Northeastern Brazil, where the winter is warm and wet. 14,16,[21][22][23][24] Such studies were typically conducted in only 1 major city in the region and have not allowed for concurrent assessments within different areas of the Northeastern region of Brazil. Moreover, they have used different eligibility criteria and methods for viral identification.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a good agreement between Real-Time PCR and nCounter for RSV (A and B) detection, reinforcing the possibility of using the latter as an alternative method for pathogen detection. Of note, RSVA strains present a high variability in the target used for detection (G protein domain) [13], also in Brazil [6], which could explain the weaker correlation observed for nCounter and Real-Time PCR, as compared to RSVB.…”
Section: Discussionmentioning
confidence: 99%